2018
DOI: 10.1002/jia2.25085
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness and budgetary impact of a dolutegravir‐based regimen as first‐line treatment of HIV infection in India

Abstract: IntroductionDolutegravir (DTG)‐based antiretroviral therapy (ART) is recommended for first‐line HIV treatment in the US and Europe. Efavirenz (EFV)‐based regimens remain the standard of care (SOC) in India. We examined the clinical and economic impact of DTG‐based first‐line ART in the setting of India's recent guidelines change to treating all patients with HIV infection regardless of CD4 count.MethodsWe used a microsimulation of HIV disease, the Cost‐Effectiveness of Preventing AIDS Complications (CEPAC)‐Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…This finding is not surprising, as we extrapolated from adult data to assume DTG-based ART would achieve lower rates of virologic failure for all children, independent of their PDR status. Prior model-based analyses have shown similar findings in adults in LMIC [ 20 , 53 ]. We found that DTG-based ART could decrease overall costs due to lower rates of virologic failure on first-line ART and thus decreased need for PI-based ART.…”
Section: Discussionsupporting
confidence: 53%
“…This finding is not surprising, as we extrapolated from adult data to assume DTG-based ART would achieve lower rates of virologic failure for all children, independent of their PDR status. Prior model-based analyses have shown similar findings in adults in LMIC [ 20 , 53 ]. We found that DTG-based ART could decrease overall costs due to lower rates of virologic failure on first-line ART and thus decreased need for PI-based ART.…”
Section: Discussionsupporting
confidence: 53%
“…(2018) modeled that DTG containing combinations is predicted to be both effective and cost-effective among sub-Saharan African countries [315]. Zheng et al (2018) also found that a generic DTG-based regimen is likely to be cost-effective in India; consequently, they believed this regimen should be recommended as initial therapy in patients newly diagnosed with HIV in India [316]. Having said this, there are still concerns regarding DTG and its combinations among LMICs.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…This, along with the reduced frequency of AEs and excellent efficacy, makes DTG an attractive replacement for EFV in first-line therapies in lowresource settings [12]. Our data show the potential benefits of DTG rollout among ART-naive and experienced patients; our group has already shown DTG to be cost-effective in lowresource settings [13]. Further research is needed to determine if widespread DTG implementation can have a greater impact on HIV prevention in the community due to quicker achievement of viral suppression [10,14].…”
Section: Discussionmentioning
confidence: 57%